Transformation Competences: Qualification Profile of Online Journalists - Konstantinova, Stela (Research Papers, 2014)
The development of professional competencies of journalists is a dynamic challenge. Journalistic work is done in a living communication medium, the Internet, which is a catalyst for changing the profession as a whole. Changes are observed both in the formal organization of work process as well as the implicit professional guiding principles. Internet and digital technologies put forward the need of “multi-professionalism.” The transforming wave which flooded media landscape and communications is especially interesting. The paper discusses the new qualification profile of online journalists and brings forward the set of specific new skills required in the field of high technology professional journalism.
Keywords: Journalism competencies; Professional profile; Communication transformations; Internet; Integrated communication system; Online journalism; Media transformations; Multimedia platform